Characterization of Thinopyrum Species for Wheat Stem Rust Resistance and Ploidy Level. Issue 6 (1st November 2014) - Zheng, Qi; Klindworth, Daryl L.; Friesen, Timothy L.; Liu, Ai‐Feng; Li, Zhen‐Sheng; Zhong, Shaobin; Jin, Yue; Xu, Steven S.
ABSTRACT: In the tribe Triticeae, several Thinopyrum species have been used as sources of resistance to stem rust (caused by Puccinia graminis Pers.:Pers. f. sp. tritici Eriks. & E. Henn., abbreviated as Pgt ) and other wheat ( Triticum aestivum L.) diseases. To identify novel sources of resistance to Pgt race TTKSK (Ug99), we evaluated and characterized the stem rust resistance of 242 accessions belonging to five Thinopyrum species, including beach wheatgrass [ Th. bessarabicum (Savul. & Rayss) A. Löve], diploid tall wheatgrass [ Th. elongatum (Host) D.R. Dewey], intermediate wheatgrass [ Th. intermedium (Host) Barkworth & D. R. Dewey], sand cough or sea wheatgrass [ Th. junceum (L.) A. Löve], and decaploid tall wheatgrass [ Th. ponticum (Podp.) Barkworth & D.R. Dewey]. These accessions were evaluated for seedling reactions to nine Pgt races (TTKSK, TTTTF, TRTTF, RTQQC, QFCSC, TCMJC, TPMKC, TMLKC, and TPPKC), genotyped with molecular markers linked to four stem rust resistance genes ( Sr24, Sr25, Sr26, and Sr43 ) derived from Thinopyrum species, and examined for ploidy levels. All accessions but one ( Th. elongatum PI 531718) were resistant to all or most races. Most of the Th. elongatum and Th. ponticum accessions showed near‐immunity to all of the races while the accessions of the other three species ( Th. bessarabicum, Th. intermedium, and Th. junceum ) had varied levels of resistance ranging from near immunity to moderate resistance. Molecular marker analysis showed that most of the markers appeared to be species‐ or genus‐specific rather than linked to a gene of interest, and thus genotyping analysis was of limited value. Comparisons of infection types of accessions based on ploidy level suggested that higher ploidy level was associated with higher levels of stem rust resistance. The results from this study substantiate that the Thinopyrum species are a rich source of stem rust resistance.